Cluster Technology as a basis for the competitive development of industries in Russia - Prokhorova, Viktoriya V.; Artemova, Elena I.; Miroshnichenko, Marina B.; Rafaelovna, Avanesova Rita; Mausurovna, Chazhaeva Maynat (Revista de la Universidad del Zulia, 2020)
In the context of globalization (Acuña, 2011) and the pressure of sanction on the national economy of the Russian Federation, the problem of the provision of competitiveness of industrial companies stands out. Economic policy in the national economy, oriented more towards the raw material component, has ceased to correspond to the modern requirements of society. In relation to this provision, new state priorities appeared, focused on improving scientific and technological development, innovation and modernization of the industrial complex, etc., which, in turn, requires the development of new mechanisms and appropriate instruments for the regulation of economic relations in the industrial sector, and the implementation of government support for the industry. However, it must be recognized that federal and regional sustainable development programs and industrial management mechanisms used in modern realities are not effective enough because they generally aim at the isolated solution of local problems. It is indisputable and obvious to all that it is impossible to reach the level of global competition without the progressive and competitive development of the main industries. One of the most constructive solutions to this problem is the cluster approach. Our country has some experience and achievements. So in 2012, employees of the Ministry of Economic Development of the Russian Federation developed a group-oriented program, the implementation of which involves twenty-five industrial groups. Cluster technologies allow the creation of synergistic and multiplier effects, which, in the end, is a boost for the development of economic growth. But despite all the preferences of the cluster approach, national cluster technologies were unable to implement their advantages, indicating the continued stagnation of industrial production. In this way, the purpose of this research is to study the possibilities of effective use of cluster technologies in the Russian industrial field.